(untitled) (Journal of Computational Mathematics, 2021)
A class of three-level six-point explicit schemes L_3 with two parameters s, p and accuracy O(τ h+h^2) for a dispersion equation U_1=aU_xxx is established. The stability condition |R|≤ 1.35756176 (s=3/2,p=1.184153684) for L_3 is better than |R| ＜ 1.1851 in [1] and seems to be the best for schemes of the same type.